Integração das práticas da logística humanitária, gestão de desastres e plano de auxílio mútuo - Moura, Eduardo Henrique de (2018)
Industrial disasters, such as fires, chemical spills and radiation are issues that are often solved through industrial protocols or other internal procedures. Humanitarian logistics, in this context, is characterized by a process based on the flow of materials and people in a limited time. In this project, the focus is to apply the concepts of logistics, ensuring the right service, so that an industrial disaster is solved at the lowest possible cost and time. Based on researches, electronic and written materials, the project reviews the temporal linearity of humanitarian logistics and contextualizing the theme with international and national disasters, such as the collapse of the tailings dam in Fundão, in Minas Gerais, or an accident with Césio-137, occurred in Goiânia. Interviews with security professionals have ensured the creation of a Framework, which explains the step-by-step of the proposed logistical model. Based on this, Logistics's preparedness and response tactics, aided by the Disaster Mutual Assistance, can guarantee faster and more effective results compared with usual methods of security from companies, as well as ensuring mutual cooperation between companies. Finally, indicators of solutions of disasters in the industry such as the Dematel decision-making ensured the creation of the theoretical model that is distinguished by joining disaster management concepts allied to Humanitarian Logistics and business participation.